#76 Simultaneous estimation of Levosulpiride and Pantoprazole in bulk and pharmaceutical formulations by RP-HPLC: Method development and validation - Thote, Lokesh (Journal of Pharmaceutical Chemistry, 2022)
A simple, precise, and rapid reverse phase HPLC- SPD 20-A method has been developed and validated to simultaneously estimate Levosulpiride (LEVO) and Pantoprazole (PANTO) in a capsule dosage form. The mixture of LEVO and PANTO was separated on a C18 column (4.6 × 250 mm) using phosphate buffer: methanol (50:50) and pH seven adjusted with dilute orthophosphoric acid a mobile phase. All separations were examined at a wavelength of 254 nm with an SPD-20A UV-Vis detector operating at 210 – 400 nm wavelengths at circumambient temperature with a flow rate of 1 mL/min. The retention time of LEVO and PANTO were 2.4686 and 4.4872; respectively, the resolution was 7.3424. The developed method can be used to routine LEVO and PANTO in a capsule dosage form.
Keywords: aaa